Off-grid rural area electrification through solar-diesel hybrid minigrids in Bangladesh: resource-efficient design principles in practice. (15th May 2015) - Chowdhury, Shahriar Ahmed; Aziz, Shakila; Groh, Sebastian; Kirchhoff, Hannes; Leal Filho, Walter
Abstract: With around 40% of the population without access to electricity but also a high penetration of solar home systems in its off grid areas, the case of Bangladesh is a very strong reference for the applicability of the Sustainable Energy Access for All (SE4A) goals. Nonetheless, while the solar home system program with 3.6 million systems has gained worldwide recognition, there are considerable limitations in the usage of such systems, in particular in the ability to provide access to higher tier energy services for productive use. Minigrids, on the other hand, could provide this access but have yet to proof both scale and commercial viability. This paper provides critical insides into the case of Bangladesh for a cost-effective route to the SE4All goals by applying practical and resource-efficient minigrid design principles. Planning and operation techniques are elaborated on in detail and concluded with a financial analysis for a hybrid solar-PV-Diesel minigrid that provides enhanced energy access in particular for productive use. In addition, implications on the business model are highlighted for developing minigrids in off grid rural areas of Bangladesh for hybrid minigrids ranging from 100 to 250 kWp while exemplarily showing how the three goals of the United Nation Sustainable Energy for All Initiative can be pursued in a mutually beneficial way. Highlights: There is a need for a wider understanding of the applications of minigrids. Minigrids are helpful tools in achieving greater energy and resource efficiency. Minigrids may cater for an enhanced productive use of the supplied electricity.